PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS TEKS FABEL SISWA KELAS VII SMP NEGERI 31 PADANG - M. Hafrison, Fitri Yunita, Erizal Gani, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The purpose of this study is(1) to determine the level of students writing skill on text fable of grade VII at SMP Negeri 31 Padang before using problem based learning model with picture series. (2) to determine the level of students writing skill on text fable of grade VII at SMP Negeri 31 Padang after using problem based learning model with picture series. (3) analyze the effect applications problem based learning model with picture series toward students writing skill on text fable grade VII at SMP Negeri 31 Padang. This type of research is quantitative with experiment methode. Based on analysis of data, using of problem based learning model with picture series toward students writing skill on text fable grade VII at SMP Negeri 31 Padang. Kata kunci : pengaruh, model Problem Based Learning, media gambar berseri, keterampilan menulis teks fabel